Drivers of the carbonate system variability in the southern North Sea : River input, anaerobic alkalinity generation in the Wadden Sea and internal processes - Schwichtenberg, Fabian (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2013)
The presented work examines the carbonate system in the southern North Sea and its sensitivity to river input, anaerobic total alkalinity (TA) generation in the Wadden Sea and internal processes by using the ecosystem model ECOHAM. Furthermore, it is aimed to reproduce observations of high TA concentrations in the German Bight that could not be reproduced in former model studies. The study consists of three main parts that examine the TA production in the southern North Sea, the impact of riverine inputs on TA in the southern North Sea and the impact of TA and DIC exported from the Wadden Sea. The TA production in the southern North Sea was examined in the first main chapter. A prognostic treatment of TA was implemented into ECOHAM that enables the calculation of TA concentration changes due to the uptake and release of nutrients into the water column as well as calcification and decalcification. It was shown that the internal processes that produced TA irreversibly were mainly driven by the uptake of allochthonous nitrate and its subsequent denitrification. In the year 2008, about 76 Gmol TA yr-1 (228 mmol TA m-2 yr-1) was produced in the entire model domain (332,050 km²). Thereof, 13 Gmol TA yr-1 (221 mmol m-2 yr-1) were produced in the validation area (59,338 km²). TA production in shelf seas on annual scales was also derived from denitrification rates in former studies. Therefore, the internal turnover of TA calculated in the study at hand was compared to simulated denitrification in the validation area and in the whole model domain in 2008. A total amount of 80 Gmol N yr-1 (241 mmol N m-2 yr-1) was denitrified in the whole model domain, whereas 22 Gmol N yr-1 (370 mmol N m-2 yr-1) was denitrified in the southern North Sea. The deviation of denitrification from TA production was also examined for the years 1977 – 2009. Denitrification exceeded the TA production in the whole model domain / southern North Sea by 13 Gmol yr-1 / 11 Gmol yr-1 on average. Furthermore, it was shown that TA production correlates ...